Functionality and disease severity in spinocerebellar ataxias - Geanison Castro da CRUZ; Marise Bueno ZONTA; Renato Puppi MUNHOZ; Neliana Maria de MELLO; Alex Tiburtino MEIRA; Maria Cristina de Alencar NUNES; Naiara Talita Guimarães ARANHA; Carlos Henrique Ferreira CAMARGO; Francisco Diego Negrão LOPES NETO; Hélio Afonso Ghizoni TEIVE (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Spinocerebellar ataxias (SCAs) are a group of neurodegenerative diseases characterized by deterioration of balance and functionality that tends to follow disease progression. There is no established link between formal clinical markers for severity and functional/balance scores that could guide rehabilitation teams. Objective: To evaluate the relationship between functional scales and ataxia severity in order to identify cutoff landmarks for functional loss and estimate the mean SARA (Scale for Assessment and Rating of Ataxia) score for the risk ratings for falls on the BBS (Berg Balance Scale). Methods: Consecutive patients with a molecular diagnosis of SCA (total 89: 31 with SCA2 and 58 with SCA3) were assessed for functionality FIM-ADL (Functional Independence Measure-activities of daily living and Lawton-IADL (instrumental activities of daily living), balance (BBS) and disease severity (SARA). Results: The main disability cutoff landmarks were that the need for supervision for FIM-ADL starts with 12 points on SARA and the need for supervision for Lawton-IADL starts with 14 points on SARA. The first items to require assistance were “expression” and “shopping”, respectively. At 20 points on SARA, patients were dependent on all FIM and Lawton items. The item with the greatest impact on distinguishing dependents from independents was “means of transport” in Lawton-IADL and the domain “locomotion” in FIM-ADL. The mean SARA score for patients classified as low risk in the BBS was 9.9 points, and it was 17.4 for medium risk and 25.2 for high risk. Conclusions: Analysis on the correlation between the severity of ataxia and functional scales can form an important guide for understanding the progression of functional dependence among individuals with SCAs.